Effectiveness of Acceptance and Commitment Therapy on Anxiety in Hypertensive Patient - Tantri Widyarti Utami; Yunani Sri Astuti (GLOBAL HEALTH SCIENCE GROUP, 2020)
Hypertension is a major problem in public health both in developed and developing countries. Emotional reactions due to hypertension are grieving, fear/anxiety, anger, depression and guilt. Anxiety is an unpleasant emotional by fear and tense and unwanted physical symptoms. Acceptance and commitment therapy (ACT) teaches clients to approach fear and anxiety more fundamentally, deeper, and in different ways Objective to knowing the effect of acceptance and commitment therapy on anxiety in hypertensive patients. Quasi-experimental design with a control group